(untitled) - Gagné, Antonnette (Québec, Canada, 1986)
Let's find out is a programme for students in the elementary schools and is based on the belief that children learn to communicate in a language through the comletion of activities which are interesting, challenging and enjoyable.
Keywords: English language,Readers ( elementary ); Textbooks for second language learners